Cytomorphological Characteristics Of Ameloblastoma By Fine Needle Aspiration Biopsy Procedure Confirmed With Histopathological Examination - Dewi Safnita; Noza Hilbertina; Yessy Setiawati (Jurnal Health Sains, 2022)
Background: Ameloblastoma is the most common benign epithelial odontogenic tumor with malignant potential and is usually located in the jaw. It constitutes about 1-3% of all tumors and cysts of jaws. This entity has a very high recurrence rate of over 50% even after wide excision. Preoperative diagnosis of ameloblastoma can be made by fine-needle aspiration biopsy (FNAB) which is used as a guide for surgical planning. Case report: We report a case of a tumor in the mandible of a 41-year-old man with a preoperative diagnosis of ameloblastoma from a fine needle aspiration biopsy. Cytological examination of FNAB was confirmed by histopathological preparation of tumor tissue. Conclusion: The fine needle aspiration biopsy cytology is a reliable procedure for the pre-operative diagnosis of ameloblastoma. Pre-operative diagnosis of ameloblastoma can be used for planning therapy and early diagnosis of recurrence cases that can improve patient survival